The Critical Discourse Analysis Model of Teun A. Van Dijk on the Online News about the Contradiction Against the Realization of the Hajj Pilgrimage of Indonesia - Eka Rahayu Putri; Anwar Efendi; Tri Lande; Yuriska Dewi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2023)
This research described the textual dimension with Teun A. Van Dijk's model on the online news text discourse. The taken theme in the text was the contradiction against the realization of the pilgrimage to Indonesia. The data of the research consisted of utterances and dialogs on online media, such as Tempo.com, Cnnindonesia.com, and Republika.co.id. On the other hand, the data source was the online news page in the form of news discourse about the contradiction against the new regulations of the hajj pilgrimage by Indonesia's government. The applied method and data collection techniques were content analysis methods with the critical discourse analysis model of Teun A. Van Dijk. The results showed that the news portals of Tempo.com, Cnnindonesia.com, and Republika.co.id had the same themes about the news on contradiction against the new hajj pilgrimage rules in Indonesia. The news dominated most analyses in this Teun A. Van Dijk's model, starting from (1) the macrostructure, (2) the superstructure, and (3) the microstructure. The undetermined elements of the news were rhetoric microstructures, such as metaphors and expressions.